States of Belonging : Immigration Policies, Attitudes, and Inclusion - Jimenez, Tomás R. (Tomás Roberto), 1975-; Dovidio, John F.; Huo, Yuen J.; Schildkraut, Deborah J., 1973- (Book collections on Project MUSE., 2021)
"This book explores interconnections between immigration policy, attitudes about immigrants and immigration, and belonging through an interdisciplinary political, sociological, and psychological framework. By focusing on immigration policy at the state level, it demonstrates how state and local governments have an active hand in shaping the resources and opportunities immigrants can access and how state and local policy influences immigrants' sense of belonging"--